Bereavement practices and staff competencies on perinatal loss at a community-based teaching hospital - Carolina Garavito; Shweta Karki; Suzanne J. Rose; Josette Hartnett (PLoS ONE, 2026)
Objective Although considerable research exists on how families experience perinatal loss, the bereavement competencies and practices at our hospital were unknown. To investigate the baseline bereavement knowledge, skills, self-awareness, and organizational support among staff working at a community-based teaching hospital, a cross-sectional study was conducted using the validated Perinatal Bereavement Care Confidence Scale (PBCCS). Methods PBCCS scores range from 1 to 5 (1 representing Strongly Disagree and 5 representing Strongly Agree). Bereavement support confidence was calculated by using mean score for each subscale to obtain total PBCCS score (score range of 32–160). A sufficient level of confidence is considered 80% or higher. Independent t-tests/ANOVA measured differences in scores for two or more groups. Results A total of 46 survey responses were received; 19 were submitted from Labor and Delivery, 13 from the Emergency Department and 5 from Maternity. 28 respondents reported that they had not received any formal education on perinatal bereavement (p = 0.006). Scores for each subscale showed low levels of bereavement support knowledge (46.45 ± 13.04), skills (23.07 ± 7.31), self-awareness (24.85 ± 7.54) and organizational support (21.73 ± 6.08). The total mean sum score was 116 (72%), indicating inadequate levels of bereavement confidence overall. Those reporting having a formal education on perinatal bereavement care were more likely to have greater self-awareness as compared to those who did not (4.23 vs 3.39, p = 0.001). Conclusion Improving perinatal loss management in a hospital setting requires a comprehensive approach that includes data-driven assessment, staff education, support, and structured protocols. Key factors influencing compassionate, dignified, and holistic bereavement care provides nursing leadership with valuable information on educational gaps to target and when formalizing protocols or workflows to address this need.